Morphological and Histochemical Changes in the Uterus Epithelium during Eggshell Formation in Quail - Atsushi Iwasawa; Mohammad A. Rahman; Tushar K. Roy; Akihiko Moriyama; Norio Yoshizaki (The Journal of Poultry Science, 2010)
The present study was conducted to determine both the site at which the eggshell matrix is produced and the critical period for its production in the oviductal uterus of the Japanese quail, Coturnix japonica. An antiserum was produced against the proteins of the 116-kDa band in electrophoretic profiles of the matrix proteins obtained from eggshells decalcified with EDTA. N-terminal amino acid sequences were very similar to those of chicken ovocleidin-116. Immunofluorescent and immunoelectron microscopic observations revealed that the 116-kDa proteins were synthesized in granular cells of the uterus mucosal epithelia, secreted between 7 and 20 h after the previous oviposition, then integrated into the structure of the eggshell matrix. Scanning electron microscopic observations revealed that 10-μm-wide posts appear on the surface of the mucosal epithelia until 21h, and disappear thereafter. The posts were less prominent in the mucosal epithelium facing the sharp end of an egg than in that facing the equator or blunt end. On the other hand, the number of pores in eggshells at the sharp end was smaller than that at the equator or blunt end. Our results indicate that air canals and/or pores are formed in the eggshell by the retreat of the posts after the establishment of eggshell.